Introducing Data-Based Modeling with Functions in a Student Laboratory:: Design and Implementation for Enhancing Statistical Literacy among Upper Secondary School Students (mathematica didactica, 2025)
This paper presents the development and implementation of a process framework for data-based modeling of functional relationships between two numeric variables, designed as an introductory experience for upper secondary school students. We describe the design process and the current concept of a student laboratory, that integrates this process model into a learning setting, following specific content and methodological design principles. Our approach aims to provide students with initial opportunities to engage with real data and mathematical modeling in meaningful contexts, thereby advancing their statistical literacy.